Pengaruh Modernisasi Sistem Administrasi Perpajakan dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Usaha Rumah Makan dan Restoran di Kota Padang - Triani, Marisa; Frima, Rini (Jurnal Ilmiah Poli Bisnis, 2024)
This research aims to analyze and prove the impact of modernization of the tax administration system and tax sanctions on taxpayer compliance in restaurant and restaurant businesses in Padang city. The type of research used is quantitative research using primary data and measurent using a likert scale (questionnaire). The sampling technique used was proportional stratified random sampling. This research uses the Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis method which was carried out with SmartPLS software version 4.1. the sample for this research was 183 taxpayer respondents from restaurant and restaurant businesses in the city of Padang. The result of this research show that the two independent variables, modernization of the tax management system and tax sanctions, have a positive and significant effect on taxpayer compliance in restaurant and restaurant businesses in Padang City. Keywords: Modernization of the tax administration system, tax sanctions, compliance of restaurant and eatery business taxpayers